Avguštin Stegenšek (1875–1920): ob stoletnici smrti - Marina Bajić; Stavbar, Vlasta; Ciglenečki, Marjeta (2021)
Avguštin Stegenšek (1875-1920): on the centenary of death. At least three reasons support the presentation of dr. Augustina Stegenška in this brochure or exhibition catalogue. This is a portrait of a young educated and talented art historian who worked in Maribor, a dedicated librarian of the Historical Society for Slovenian Styria, for whom the collection of archival data was a real challenge, and accurate recording led to many research discussions and contributions. The University Library of Maribor keeps a part of Stegenšek's written legacy, which it strives to digitize and in this way make it accessible. The third reason is in cooperation with art history students at the Faculty of Arts, the University of Maribor, with whom the library under the mentorship of Assoc. prof. dr. Marjeta Ciglenečki has been participating in many projects or exhibitions for many years. This time the collaboration was marked by the centenary of Stegenšek's death with a display of his extensive cultural and historical oeuvre. Selected interpretations of Stegenšek's art history articles or books contributed by students of the Faculty of Arts of the University of Maribor are an interesting starting point for further research in this field.